The development of research framework for the decision to participate in stock market: a systematic review of literatures from 2011-2021 / Ho Thong Koh and Mohd Nazri Mohd Noor - Ho, Thong Koh; Mohd Noor, Mohd Nazri (UiTM Press, 2021)
The purpose of this paper is to understand stock market participation among individual investors. This paper has established a descriptive systematic-analysis of the empirical literature from journal indexed by Scopus, ISI ad ERA with an emphasis on the conceptualization and antecedents of stock market participation. Based on the review of past literature, this paper suggested social alignment, fundamental stock literacy, trust on institution and stock value expectation that would relate to stock market participation. The recommended framework may serve as a practical guide for stock broking firm to understand the behaviour of individual investors, encourage participation in the stock market and aid in the development of marketing strategies in competitive market.